Impact of fixed dental prosthesis on neuroimaging: assessment of artefacts - Kazmi, Syed Murtaza Raza; Kaleemi, Raima; Jamal, Wafa Zehra; Azeemuddin , Dr Muhammad; Farhan Raza Khan (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the frequency and extent of artefacts in magnetic resonance imaging and/or computed tomography scans of head caused by fixed dental prosthesis. Method: The retrospective study was conducted at Aga Khan University Hospital from July to December 2021, and comprised magnetic resonance imaging and/or computed tomography scans from January 2015 to December 2020 of the head of individuals with existing fixed dental prosthetic work at the time of exposure. They were analysed for the presence of artefacts. The association between artefacts and the presence of fixed dental prosthesis was explored. Data was analysed using SPSS 23. Results: Of the 297 images evaluated, 173 (58%) were magnetic resonance imaging scans, and 124(42%) were computed tomography scans. The most common artefacts was grade I 148(49.8%), followed by grade II 140(47.1%) and grade III 9(3%). There was no significant association between fixed dental prosthesis and the artefacts (p>0.05). Conclusion: There should be no reservations in placing fixed metal prosthesis in individuals on account of future brain scans. Key Words: Fixed dental prosthesis, Imaging, CT scan, MRI, OPG, Artefacts.